Avaliação do potencial anticorrosivo de tiossemicarbazonas solubilizadas em sistemas microemulsionados - Moura, Elaine Cristina Martins de (2009)
In this work thiosemicarbazones [4-N-cinnamoyl-thiosemicarbazone (CTSC), 4-N-(2'-methoxycinnamoyl)-thiosemicarbazone (MCTSC), and 4-N-(4'-hydroxy-3'-methoxybenzoyl)-thiosemicarbazone (HMBTSC)] were solubilized in an microemulsion system (ME_OCS) which is rich in aqueous phase (O/W system). The system ME_OCS was obtained with saponified coconut oil (OCS) as (surfactant), butanol (cosurfactant), and kerosene as oil phase (Fo), using 40% of C/T (cosurfactant/surfactant), 5% of Fo and 55% of aqueous phase. The microemulsions systems CTSC_ME_OCS, MCTSC_ME_OCS and HMBTSC_ME_OCS effectiveness on a AISI 1020 carbon steel corrosion inhibition process were evaluated in a saline solution (NaCl 0.5%), using a galavostatic method. The tested thiosemicarbazones (TSC) showed highest inhibitors effects (85.7% for CTSC_ME_OCS, 84.0% for MCTSC_ME_OCS, and 83.3% HMBTSC_ME_OCS) at lower concentrations [0.19% of CTSC, 0.07% (MCTSC), and 0.26% (HMBTSC)]. Comparatively, the surfactant OCS (solubilized in H2O) as well as the system ME_OCS showed lower efficacy [71% for OCS (at 0.20 - 0.25% of concentration) and 74% for ME_OCS (at 0.5% of concentration)]. Since the microemulsion systems ME_OCS showed satisfactory interfacial adsorption, the greatest inhibitory effect of those TSC_ME_OCS systems could be correlated to both chemical composition of each tested TSC (which is rich in heteroatoms and aromatic ring) and also the presence of the surfactant OCS